P486 Response to vedolizumab therapy in patients with inflammatory bowel disease: Impact of drug levels, anti-drug antibodies and α4β7 target occupancy. (16th January 2018) - Ungar, B; Kopylov, U; Yavzori, M; Fudim, E; Picard, O; Lahat, A; Coscas, D; Waterman, M; Haj-Natour, O; Orbach-Zingboim, N; Mao, R; Chen, M; et al.
Abstract: Background: Real-life pharmacokinetics/pharmacodynamics data of vedolizumab are still scarce. Methods: Vedolizumab/AVA levels were measured in 106 prospectively followed inflammatory bowel disease (IBD) patients receiving vedolizumab induction and maintenance therapy. Fluorescent conjugated-vedolizumab was used to investigate α4β7 occupancy on effector-memory T cells in peripheral blood (PB) and intestinal lamina propria (LP) by FACS analysis. Results: Week 6 vedolizumab levels were higher in patients in clinical remission than in those clinically active (40.2 µg/ml vs. 29.7 µg/ml, respectively, p = 0.05). Drug levels were significantly higher among patients with normal compared with elevated C-reactive protein values during maintenance treatment (21.8 µg/ml vs. 11.9 µg/ml, respectively, p = 0.0006). Most other outcomes were not associated with drug-levels at any of the time-points examined. The rate of AVA was 17% during induction and 3% during maintenance, but did not correlate with clinical outcomes. Flow-cytometry analysis of PB memory T cells ( n = 36) showed near-complete occupancy of target α4β7 at Weeks 2 and 14 and during maintenance, regardless of response status or drug levels. In the intestine of healthy and active IBD controls ( n = 14), most CD3+CD45RO+ memory T cells were found to express α4β7, whereas in vedolizumab-treated patients ( n = 15) these intestinal α4β7+ cells were nearly absent or blocked in both responding and non-responding patients (72%, IQR 56–81% vs. 5.6%, IQR 4.4–11.2%, respectively, p < 0.0001). Conclusions: In this large real-life prospective IBD cohort, vedolizumab drug levels were modestly associated with some clinical-biomarker outcomes. A near-complete occupancy of blood and intestinal α4β7 was exerted by vedolizumab through a wide-range of drug levels, regardless of clinical outcomes. These data suggest the need to explore alternative mechanisms possibly underlying response and lack-of-response to vedolizumab.